Walking the line: The fate of nanomaterials at biological barriers. (August 2018) - Meng, Huan; Leong, Wei; Leong, Kam W.; Chen, Chunying; Zhao, Yuliang
Abstract: Biological systems have developed an efficient multi-tiered defense system to block foreign substances such as engineered nanomaterials (NMs) from causing damage. In a pathological scenario, the disease itself may also pose additional barriers due to the imbalance between abnormal cells and their surrounding microenvironment, and NMs could behave similarly or differently to classic foreign substances, depending on their unique characteristics. Thus, understanding the mechanisms that govern the fate of NMs against these biological barriers, including the strategies that can be used to shift their fate between access and blockage, become key information for NMs design. In this manuscript, we first describe the biological barriers that NMs may encounter, and further discuss how these biological barrier interactions could shift the fate of NMs between toxicity and therapeutic potential. A list of effects that may influence NMs access at nano/bio interface are presented and discussed, followed by personal insights on the important nano/bio topics that require additional research for a better understanding of NM/biological barrier interactions.